Speak - Anderson, Laurie Halse (New York : Farrar Straus Giroux, 1999)
A traumatic event near the end of the summer has a devastating effect on Melinda's freshman year in high school.
Michael L. Printz Honor Book, 2000
Keywords: Emotional problems -- Fiction; High schools -- Fiction; Schools -- Fiction; Rape -- Fiction